Faktor-faktor yang Berhubungan dengan Kejadian ISPA pada Balita di Wilayah Kerja Puskesmas Pematang Raya Kabupaten Simalungun Tahun 2025 - Purba, Gesika Alfiati (Jurnal Penelitian Kesmasy, 2025)
Acute Respiratory Infections (ARI) remain a global public health burden and are a leading cause of morbidity and mortality in children under five. In Indonesia, ARI incidence among toddlers remains high, with several modifiable risk factors involved. This study aimed to examine Factors Related to the Incidence of ARI in Toodlers in Working Area Pematang Raya Public Health Center Simalungun District in 20255. A quantitative, cross-sectional study was conducted involving 88 respondents selected through simple random sampling. Data were collected using structured questionnaires and analyzed using univariate and bivariate analyses with Chi-square tests at a 5% significance level. The study found that 63.6% of toddlers had experienced ARI. Significant relationships were identified between ARI and maternal knowledge (p<0.005), family smoking habits (p<0.005), immunization status (p<0.005), and exclusive breastfeeding (p<0.005). The study emphasizes the importance of maternal education, complete immunization, exclusive breastfeeding, and reducing household smoking exposure in mitigating ARI risk. Strengthening health promotion and preventive efforts is crucial to lowering ARI prevalence in this vulnerable population.